2010
DOI: 10.1103/physrevb.82.064512
|View full text |Cite
|
Sign up to set email alerts
|

Structure and physical properties of the noncentrosymmetric superconductorMo3Al2C

Abstract: We have synthesized polycrystalline samples of the noncentrosymmetric superconductor Mo 3 Al 2 C by arc and RF melting, measured its transport, magnetic and thermodynamic properties, and computed its band structure.Experimental results indicate a bulk superconducting transition at T c ~ 9.2 K, while the density of states at the Fermi surface is found to be dominated by Mo d-orbitals. Using the measured values for the lower critical field H c1 , upper critical field H c2 , and the specific heat C, we estimated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
101
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 33 publications
13
101
2
1
Order By: Relevance
“…We note that conventional superconductivity in NCSCs is not uncommon [50][51][52][53] , despite the theoretical possibility of exotic behavior. It has been suggested that the presence of substantial electronic correlations is a necessary ingredient for appreciable spin-triplet pairing in NCSCs 54 , which is one possible explanation for the apparent lack of unconventional behavior in the uncorrelated compound CaIrSi 3 .…”
Section: λ 4γµmentioning
confidence: 99%
“…We note that conventional superconductivity in NCSCs is not uncommon [50][51][52][53] , despite the theoretical possibility of exotic behavior. It has been suggested that the presence of substantial electronic correlations is a necessary ingredient for appreciable spin-triplet pairing in NCSCs 54 , which is one possible explanation for the apparent lack of unconventional behavior in the uncorrelated compound CaIrSi 3 .…”
Section: λ 4γµmentioning
confidence: 99%
“…5 , CeIrSi 3 (T c = 1.6 K under pressure) 6 , Li 2 Pt 3 B (T c = 2.6 K) 7 and Mo 3 Al 2 C (T c = 9.2 K) 8,9 . For several NCS SCs solid evidence for an odd-parity component in the SC order parameter has been extracted from critical magnetic fields exceeding the spin-singlet Pauli paramagnetic limit and/or line or point nodes in the SC gap function…”
mentioning
confidence: 99%
“…Li 2 Pd 3 B is an s-wave superconductor, while the stronger ASOC in Li 2 Pt 3 B enhances the triplet component, producing line nodes in the gap, as revealed by the linear temperature dependence of the magnetic penetration depth λ(T ) at low T [11,12]. Mo 3 Al 2 C (NCS chiral space group P 4 1 32) is a strongly coupled superconductor with a T c of 9 K. NMR and electronic heat capacity data, along with a pressure-enhanced T c , suggest Mo 3 Al 2 C has a nodal gap with singlet-triplet mixing [13,14].…”
mentioning
confidence: 99%